Qualitative Phenomenological Study on Nurse Anesthetists’ Experience of Patient Safety in High-Workload Operating Rooms - Handoko, Lukas; Irawan, Agustinus Purna (Universitas Pakuan, 2025)
This study explores the lived experiences of nurse anesthetists in maintaining patient safety under high workload conditions in the operating room. Using a qualitative phenomenological design, data were collected through in-depth interviews with ten nurse anesthetists working in a general hospital, each with a minimum of two years of clinical experience. Thematic analysis identified five major themes: (1) high workload characterized by intensive surgical schedules and limited recovery time; (2) the physical and psychological consequences of workload on nurse well-being and patient safety; (3) adaptive coping mechanisms including time management, spirituality, and interprofessional communication; (4) situational preparedness in responding to emergencies; and (5) the essential role of institutional support in sustaining performance and safety outcomes. Senior nurses tended to rely on professional experience, emotional regulation, and spiritual strength, whereas junior nurses required closer supervision and structured guidance. The findings reveal that excessive workload significantly compromises concentration, emotional balance, and the ability to maintain optimal care. Both individual coping strategies and strong organizational backing are vital for ensuring patient safety and sustaining nurse anesthetist resilience in high-pressure clinical environments. This study provides critical insights for developing human-centered hospital policies and fostering a supportive culture that promotes staff well-being and patient safety.